Towards an Understanding of Low-Income Individuals’ Financial Resiliency: Exploration of Risk Preferences, Personality Traits, and Savings Behavior - Parra, Carlos M.; Poudel, Ranjita; Sutherland, Matthew (Journal of Economics and Behavioral Studies, 2021)
The Coronavirus disease 2019 (COVID-19) pandemic has helped expose and exacerbate individuals’ and households’ financial vulnerability worldwide. Meanwhile, behavioral elements affecting low-income populations’ ability to save and become more financially resilient have yet to receive sufficient academic attention. This exploratory study aims at the beginning to help elucidate the determinants of low-income individuals’ real-life savings behavior by utilizing laboratory performance measures (to characterize participants’ risk preferences by using the Balloon Analog Risk Task – BART, in study 1), as well as self-report surveys (to characterize participants’ personality traits, in study 2). Combining results from both studies, latent personality traits (i.e., attitude towards risk, perseverance, distractibility, and state anxiety) are found to affect the risk preferences of low-income individuals (captured using a novel BART performance measure indicative of an individual’s strategic risk preference adaptation), which in turn impact their ability to successfully complete matched savings programs and, thus, their ability to save and enhance their financial resilience.